Trends in Ambulatory Prescribing of Antiplatelet Therapy among US Ischemic Stroke Patients: 2000–2007 - Sudeep Karve; Deborah Levine; Eric Seiber; Milap Nahata; Rajesh Balkrishnan (Advances in Pharmacological Sciences)
Objective. Study objectives were to assess temporal trends and identify patient- and practice-level predictors of the prescription of antiplatelet medications in a national sample of ischemic stroke (IS) patients seeking ambulatory care. Methods. IS-related outpatient visits by adults were identified using the National Ambulatory Medical Care Survey and National Hospital Ambulatory Medical Care Survey for the years 2000–2007. We assessed prescribing of antiplatelet medications using the generic drug code and drug entry codes in these data. Temporal trends in antiplatelet prescribing were assessed using the Cochran-Mantel-Haenszel test for trend. Results. We identified 9.5 million IS-related ambulatory visits. Antiplatelet medications were prescribed at 35.5% of visits. Physician office prescribing of the clopidogrel-aspirin combination increased significantly from 0.5% in 2000 to 22.0% in 2007 (P=0.05), whereas prescribing of aspirin decreased from 17.9% to 7.0% (P=0.50) during the same period. Conclusion. We observed a continued increase in prescription of the aspirin-clopidogrel combination from 2000 to 2007. Clinical trial evidence suggests that the aspirin-clopidogrel combination does not provide any additional benefit compared with clopidogrel alone; however, our study findings indicate that even with lack of adequate clinical evidence physician prescribing of this combination has increased in real-world community settings.